Implication of Interleukin-12/15/18 and Ruxolitinib in the Phenotype, Proliferation, and Polyfunctionality of Human Cytokine-Preactivated Natural Killer Cells - Terrén, Iñigo; Mikelez, Idoia; Odriozola, Irati; Gredilla, Andrea; González, Javier; Orrantia, Ane; Vitallé, Joana; Zenarruzabeitia, Olatz; Borrego, Francisco (Frontiers in Immunology, 2018)
A brief in vitro stimulation of natural killer (NK) cells with interleukin (IL)-12, IL-15 and IL-18 endow them a memory-like behavior, characterized by higher effector responses when they are restimulated after a resting period of time. These preactivated NK cells, also known as cytokine-induced memory-like (CIML) NK cells, have several properties that make them a promising tool in cancer immunotherapy. In the present study, we have described the effect that different combinations of IL-12, IL-15 and IL-18 have on the generation of human CIML NK cells. Our data points to a major contribution of IL-15 to CIML NK cell mediated cytotoxicity against target cells. However, the synergistic effect of the three cytokines grant them the best polyfunctional profile, that is, cells that simultaneously degranulate (CD107a) and produce multiple cytokines and chemokines such as interferon (IFN)γ, tumor necrosis factor (TNF)α and C-C motif chemokine ligand (CCL)3. We have also analyzed the involvement of each cytokine and their combinations in the expression of homing receptors CXCR4 and CD62L, as well as the expression of CD25 and IL-2-induced proliferation. Furthermore, we have tested the effects of the Jak1/2 inhibitor ruxolitinib in the generation of CIML NK cells. We found that ruxolitinib-treated CIML NK cells expressed lower levels of CD25 than non-treated CIML NK cells, but exhibited similar proliferation in response to IL-2. In addition, we have also found that ruxolitinib-treated NK cells displayed reduced effector functions after the preactivation, which can be recovered after a 4 days expansion phase in the presence of low doses of IL-2. Altogether, our results describe the impact that each cytokine and the Jak1/2 pathway have in the phenotype, IL-2 induced proliferation and effector functions of human CIML NK cells.